PELAGIC FISHERY RESOURCES OF LAWSON’S BAY, WALTAIR - Rao, K Venkata Subba; Rao, V Ramamohana; Mojumder, P; Rao, T Appa; Reuben, S; Dan, S S; Rao, B Narayana (Indian Journal of Fisheries, 2011)
At Lawson’s B;y, the gears employed are shoreseines, boatseines, hooks and lines, surface g!llnets and bottom-set nylon nets. During the period 1970 to 1974, the estimated total annual landings by all gears were 654. 8, 62?.0’, 577.<)8, 542.4 and 637.3 tonnes, respectively. The ca’iches by hooks and lines alone accounted for 50-60% of the tot.l landings during the period. Seasonal abundance of fish showed correlations with hydrological and planktological conditions and the food avalable in environment. Far pelagic fi&hes, high catch rates were obtained during Novem’ber to May and to a lesser extent during July-September. Prawns were caught in greater proportions by gillnets than by boat seines, the former being employed during May-September period. The adverse effects arising out of the introduction of bottom-set gillnets in the fishery are discussed.